PUNISHING DOMESTIC HOUSEBREAKING - Shannon Hoctor (Obiter, 2023)
Housebreaking is pre-eminently a crime of violation. From the earliest times the interest of a person in the safe and private habitation of his home has been treated reverently and regarded as deserving of special protection by the law. This is reflected in the original rationale for the crime, in its Common Law manifestation, as an offence against the habitation. Domestic housebreaking, consisting of the breaking and entry into a dwelling for the purposes of committing a crime within, is thus the classic form of the housebreaking crime, involving the violation of the dweller's sanctuary from external attack (for, as Coke has enquired, “where shall a man be safe if it be not in his house?”). The consequences of domestic housebreaking are not only (in the typical case) material loss, but a significant degree of psychological or emotional trauma. The victim has to contend with more than just the initial shock however. Research has indicated that feelings of fear and nervousness, along with changes in eating and sleeping patterns, may persist long after the housebreaking has taken place. Where the incident of housebreaking goes beyond simple transgression of property interests, with a concomitant infringement of the victim's territoriality, and results in a confrontation between housebreaker and victim, it follows that the resulting harm may be notably amplified.It brooks no denial that housebreaking is a paradigmatic criminal act. This is reflected in its ubiquitous presence as a substantive offence in all jurisdictions based on English “Common Law”, usually as “burglary” or “breaking and entering”. Moreover, the conduct associated with housebreaking is criminalized in civil law jurisdictions, usually as either an aggravated form of the crime of theft or a trespass offence. Given the consensus that the conduct associated with the housebreaking crime is deserving of criminalization, this leads as a matter of course to the issue of punishment – what factors ought to be taken into account in determining the sentence of the convicted housebreaker?